Implementation of the 8+i link and match vocational school program - Wahjusaputri, Sintha; Rahmanto, Muhammad Arifin; Suciani, Suciani; Kustantini, Susi (Journal of Education and Learning (EduLearn), 2024)
This research aims to create the 8+i link and match model as an embodiment of a healthy learning ecosystem between schools and the worlds of business and industry. The research technique is a mix of quantitative and qualitative research methodologies. The qualitative technique develops a basic list of success characteristics using meta-ethnography, whereas the quantitative approach defines the link between the variables under examination by establishing or building many latent variables that explain the relationship between variables using Aiken's formula and SPSS version 26. The study's findings demonstrate the success of the 8+i link and match model between Muhammadiyah 1 Ciputat vocational high school/Sekolah Menengah Kejuruan (SMK) Muhammadiyah 1 Ciputat and industry in generating efficiency and mutual benefits for both parties, not just ordinary collaboration, but intense collaboration from the curriculum development, learning, and industrial work practices designed collaboratively. The Implication of the 8+i link and match model if correctly implemented is that the industry will profit because the training expenses is reduced, and vocational high schools will benefit because their graduates is absorbed by the industry. Recommendations for the vocational high school curriculum must include schools, and industry, also Teaching personnel must include practitioners from industry as well as instructors from schools.